Quality of life in pregnant women with subclinical hypothyroidism: clinical management gaps - Zahra Panahi; Marziye Sadeghi Gogheri; Mohadese Dashtkoohi; Mohammadamin Noorafrooz; Nasim Eshraghi; Marjan Ghaemi; Fahimeh Ghotbizadeh Vahdani; Razieh Akbari; Mohammad Sadeq Najafi; Mohammadamin Parsaei; Alireza Imani Porshokouh; Bahram Salmanian; et al. (Thyroid Research)
Abstract Background Subclinical hypothyroidism (SCH) during pregnancy affects a significant proportion of women, yet its impact on maternal well-being remains insufficiently explored. Current diagnostic and treatment guidelines focus primarily on thyroid-stimulating hormone (TSH) levels, often overlooking the broader implications of SCH on maternal quality of life (QoL). This narrow focus may lead to missed opportunities for interventions that could enhance the overall well-being of this population. In this study, we aimed to assess the impact of SCH on QoL in first-trimester pregnant women and determine whether untreated SCH with TSH levels between 2.5 and 4 µIU/mL compromises maternal well-being. Materials and methods This is a cross-sectional study conducted on pregnant women during first trimester of pregnancy. Participants were divided into SCH and euthyroid groups based on TSH levels. Data regarding health-related quality of life (HRQoL) was collected using a questionnaire previously described and validated for study population. Data were analysed using descriptive statistics, comparative tests, and multiple linear regression. Results Among 409 pregnant women, those with SCH demonstrated notably lower physical and mental HRQoL compared to those with normal thyroid function. The physical component score was 14.59 ± 3.63 in the SCH group versus 15.96 ± 3.44 in the euthyroid group (p < 0.001), while the mental component score was 20.24 ± 4.24 in the SCH group compared to 22.39 ± 4.55 in the euthyroid group (p < 0.001). This decline affected all areas assessed, including general and mental health, physical function, bodily pain, and social functioning. TSH levels emerged as a significant predictor of overall HRQoL using regression analysis (B coefficient − 1.30,95% CI: -2.08 to -0.52; p = 0.001). Conclusion This study demonstrates that SCH significantly compromises the HRQoL in pregnant women. The findings underscore the necessity for comprehensive management strategies that not only prioritize the optimization of thyroid function but also address the significant QoL impairments observed in SCH. Given the current lack of treatment recommendations for SCH in pregnant women based on TSH alone, QoL should be incorporated into clinical guidelines to provide more patient-centered care.